Analisis Video Pembelajaran Simbol Pancasila Melalui Aplikasi Canva Kelas 1 SDN Plamongansari 02 - Ahlul Mufid Himayanti; Muhammad Prayito; Joko Sulianto; Sri Wikyuni (JANACITTA, 2023)
Education is an important element in human life. various technological developments participate in the role of education. the use of technology is important to convey information as a learning medium. Processlearning is an arrangement of elements, including people, materials, facilities, equipment, and processes, which interact and communicate with each other to achieve learning objectives. From this study is to convey learning by utilizing video editing applicationCanva on learning the symbols of Pancasila. in this study, carried out by qualitative methods through observation and interviews. Pancasila symbols made using the Canva application. Learning Pancasila symbols through learning videos made with applicationsCanva effective for increasing students' understanding of Pancasila values. Students are more interested and easy to understand learning material when it is presented in an interesting and interactive video. Learning Pancasila symbols through videolearning made with Canva can be an effective choice to increase students' understanding of Pancasila values. The results of this study can be used as recommendations for teachers to develop more innovative and interesting learning media to increase learning effectiveness.   Pendidikan merupakan unsur penting dalam kehidupan manusia.  berbagai perkembangan teknologi ikut serta dalam peran pendidikan.  pemanfaatan teknologi menjadi hal penting untuk menyampaikan informasi sebagai media pembelajaran.  Proses pembelajaran adalah susunan unsur-unsur, termasuk orang, bahan, fasilitas, peralatan, dan proses, yang saling berinteraksi dan berkomunikasi untuk mencapai tujuan pembelajaran..  tujuan dari kajian ini adalah untuk menyampaikan pembelajaran dengan memanfaatkan aplikasi edit video Canva pada pembelajaran simbol-simbol Pancasila.  dalam kajian ini, dilakukan dengan metode kualitatif melalui observasi dan wawancara.  simbol-simbol Pancasila yang dibuat menggunakan aplikasi canva. Pembelajaran simbol-simbol Pancasila melalui video pembelajaran yang dibuat dengan aplikasi Canva efektif untuk meningkatkan pemahaman siswa tentang nilai-nilai Pancasila. Siswa lebih tertarik dan mudah memahami materi pembelajaran ketika disajikan dalam bentuk video yang menarik dan interaktif.pembelajaran simbol-simbol Pancasila melalui Video pembelajaran yang dibuat dengan Canva dapat menjadi pilihan efektif untuk meningkatkan pemahaman siswa terhadap nilai-nilai Pancasila . Hasil kajian ini dapat dijadikan rekomendasi bagi para guru untuk mengembangkan media pembelajaran yang lebih inovatif dan menarik untuk meningkatkan efektivitas pembelajaran.